Perceived usefulness and behavioural intention to use electronic law information resources by postgraduate law students in selected universities in South-west, Nigeria (2017)
Legal research is highly information intensive. For postgraduate law students to carry out effective legal research and practice, they need legal information in abundance. Electronic law information resources have the advantage of easy access and convenience. To take the benefit of these advantages, however, there is the need for postgraduate law students in Nigerian universities to develop good perception of the usefulness of and have the intention to use electronic law information resources. It is against this background that the study investigated the perceived usefulness and behavioural intention as determinants of electronic law information resources use by postgraduate law students in three universities in South-west Nigeria. The study adopted the survey research design with the questionnaire as instrument for data collection. Total enumeration method was used to select 336postgraduate law students in the three universities. Data analysis was undertaken using simple descriptive statistics and Pearson Product Moment Correlation. The findings of the study revealed that LexisNexis, West law and e-journals were some of the electronic law information resources frequently used by postgraduate law students. It was also established that perceived usefulness had a significant relationship with use of electronic law information resources by postgraduate law students and there was a significant relationship between behavioural intention and use of electronic law information resources.